Epidemiological investigation of peste des petits ruminants virus infection in goat with therapeutic managementat at Bera upazila of Pabna in Bangladesh (Progressive Agriculture, 2017)
Peste des petits ruminants (PPR), a fatal viral disease of goats causes high mortality and large economic losses, and is considered as one of the major constrains of goat farming worldwide.This study was undertaken to determine the prevalence, alteration of vital signs and effective therapeutics of PPR affected goats inBeraupzilla ofPabna district, Bangladeshduring the period of November 2014 to April 2015. A total number of 465 diseased goats were clinically examined of which 253 (54.41%) were found to be affected with PPR. The highest prevalence (72.27%) was found in Black Bengal goats whereas 35.04% and 27.78% prevalence were found in Jamunapari and Cross breed goats respectively. In case of Black Bengal goats51.78% affected goats were aged between 0-7months. In case ofJamunapari 51% affected goats aged between 8-14 months. Female goats were more susceptible (65%) as compared to males. About 60%Black Bengal goats had a body temperature range of 104-105.9 ?F. Over half of the study populations were in normal range of respiration rate.65%cross breeds heart rate was recorded in 91-110/minute range group that was higher in comparison to other breeds.The response totreatment following parenteral (I/M) administration of Sulphadimidine was higher (58%) than parenteral (I/M) OxytetracyclineHCl (50%) and Gentamycin Sulphate (46%) administration. All these findings revealed that, the prevalence of PPR depends on specific breed and age groupsand Sulphadimidine is the most effective drug choice in PPR treatment.Progressive Agriculture 28 (2): 114-119, 2017